(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The interdependence of folklore and literature is an urgent problem of current literary criticism in the aspect of the formation of world culture. An important task of modern science involves identifying difficult ones. unique, historically determined patterns of literature’s appeal to folklore in different eras. the concept of the dynamics of these connections.